ESTRUTURA FLORAL EM ESPÉCIES DE PASSIFLORA COM DIFERENTES SÍNDROMES DE POLINIZAÇÃO - Mattos, Leticia De (2017)
Passifloraceae Juss. Ex Roussel is a angiosperms family with tropical and subtropical distribution, their reproduction may involve both self-compatible and self-incompatible systems, there are also cases where both may occur in the same species. The behavior of the pollinators can be influenced by the chemical and morphological characteristics of the flowers. Among the rewards to the pollinator is nectar. This study aimed to analyze the anatomy of the flower tube of different species of Passiflora L., related to the pollination syndrome. The concentration of sugars in nectar was measured in field with a refractometer. The anatomical studies were performed with samples already fixed, submitted in plastic resin inclusion medium, sectioned in a rotating microtome and analyzed under a light field microscope. The concentrations of sugar in the nectar presented variation according to the collection schedule. The anatomical analysis evidenced the presence of idioblasts containing calcium oxalate and cells with phenolic compounds. The exudation of nectar occurs by the epidermis itself in Passiflora tholozanii Sacco, P. guazumifolia Juss., P. suberosa L., by modified stomata and by the epidermis itself in P. villosa Vell., P. tenuifila L., P. caerulea L., P. actinia Hooker, P. galbana Masters, P. amethystina Mikan. By means of papillae in P. mixta L., P. tripartita var. mollissima (Kunth) Holm-Niels. & P. Jorg., P. tarminiana Coppens & V.E. Barney. The starch was present throughout the secretory tissue, before initiating the secretion was near the conducting vessels. The phenolic compounds produced act in the defense against herbivory and nectar scavengers. The anatomy evidenced that plants with the same pollination syndrome have similar anatomical characteristics.